2014
DOI: 10.3109/00365548.2014.974206
|View full text |Cite
|
Sign up to set email alerts
|

High faecal calprotectin levels in intestinal tuberculosis are associated with granulomas in intestinal biopsies

Abstract: ITB patients with granulomas on histology have high levels of faecal calprotectin and CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Raised FCP levels have been found to be associated with chronic giardia infection and microscopic duodenal inflammation . Studies have demonstrated high levels of FCP in patients with intestinal tuberculosis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raised FCP levels have been found to be associated with chronic giardia infection and microscopic duodenal inflammation . Studies have demonstrated high levels of FCP in patients with intestinal tuberculosis …”
Section: Discussionmentioning
confidence: 99%
“…35 Studies have demonstrated high levels of FCP in patients with intestinal tuberculosis. 36 There is scarcity of data regarding the usefulness of FCP in patients with UC from South Asian countries. To the best of our knowledge, our study is the second study conducted in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these were initially diagnosed as nonspecific ulcers and two patients with Crohn’s disease, and they were finally diagnosed with Crohn’s disease and tuberculosis, respectively, and treated accordingly. The use of newer surrogate markers of inflammation such as serum calprotectin 15 16 and lactoferrin 17 in these nonspecific ulcers could have aided in early diagnosis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding multiorgan tuberculosis, it has been shown that high fecal CLP levels could differentiate intestinal from pulmonary tuberculosis [ 68 ]. High fecal CLP levels in intestinal tuberculosis were associated with granulomas in intestinal biopsies [ 79 ]. Patients with combined pulmonary and intestinal tuberculosis had the highest serum CLP (6.5 mg/L) and presented more severe disease [ 80 ].…”
Section: Clp In Respiratory Infectionsmentioning
confidence: 99%